For the 70th birthday of Prof. Száz - Vidovics Dancs, Ágnes (Public Finance Quarterly, 2023)
Corvinus University, Budapest Stock Exchange, National Bank of Hungary, Training Center for Bankers, Sapientia University – fragments from the last 30 years